2016
DOI: 10.3389/fmed.2016.00016
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Study on the Risk of Bacteremia in Banding versus Sclerotherapy of Esophageal Varices

Abstract: BackgroundEsophageal variceal banding may be less likely to cause bacteremia than sclerotherapy. The existing data about the frequency of bacteremia after esophageal variceal banding are conflicting, and few studies include both banding and sclerotherapy.AimsWe conducted a prospective randomized controlled trial to compare the frequency of bacteremia after esophageal variceal banding and sclerotherapy.MethodsOver a 2-year period, patients with liver disease admitted for upper gastrointestinal bleeding or for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
1
1
0
1
Order By: Relevance
“…In the current study, about 48% of patients had at least one chronic illness, whereas the most frequent one was chronic liver disease (44%), hypertension (12%), diabetes mellitus (12%) and cancer (5%). Similar data was revealed by Zucherman et al 9 who showed Patients who have had endoscopic treatment for esophageal varices and chronic liver disease are more likely to develop bacteremia and infections.…”
Section: Discussionsupporting
confidence: 82%
“…In the current study, about 48% of patients had at least one chronic illness, whereas the most frequent one was chronic liver disease (44%), hypertension (12%), diabetes mellitus (12%) and cancer (5%). Similar data was revealed by Zucherman et al 9 who showed Patients who have had endoscopic treatment for esophageal varices and chronic liver disease are more likely to develop bacteremia and infections.…”
Section: Discussionsupporting
confidence: 82%
“…Recurrent variceal bleeds or post-injection ulceration can cause re-bleeding. When compared to EBL, EVS has been linked to a higher risk of complications, including pleuropulmonary complications, bleeding, and infection [ 78 ].…”
Section: Prevention and Management Of Variceal Bleedingmentioning
confidence: 99%
“…Los procedimientos endoscópicos invasivos (p. ej., ligadura o escleroterapia endoscópica de várices esofágicas) pueden incrementar la posibilidad de infección en pacientes cirróticos 58 .…”
Section: Pacientes Con Cirrosisunclassified